Hydrogeochemical data from carbonate springs as an aid for delimiting catchment areas in the Rovte region, Central Slovenia - Vanessa E. Johnston; Filip Šarc; Katarzyna Wątor; Bojan Otoničar (Journal of Hydrology: Regional Studies)
Study regions: The Rovte region, Central Slovenia, is a rural region where karst spring waters are often used for drinking water consumption and irrigation. Study focus: In karst regions, water quickly reaches the subsurface through features ranging from thin fractures to large conduits; as such, this rapid flow leaves karst areas particularly vulnerable to pollutants. This range of permeability and frequently mixed lithologies means that catchment areas in karst regions are often difficult to determine. Here, we present a year-long dataset of hydrogeochemical monitoring of six karst springs and one river, alongside detailed geological data. The aim was to test if water geochemistry can be used to determine the geological units through which the waters flowed, and if this knowledge can help locate plausible catchment areas for springs in karst regions. New hydrological insights for the region: We show that subtle differences in water geochemistry (including major ions, electrical conductivity, pH) and discharge rates permitted the identification of the geological units (including limestones, dolostones, marly limestones, and siliciclastics) through which the waters flowed. This led to significant modifications to the topographically-modeled catchment areas. We, therefore, advocate using water geochemistry to delineate realistic catchment areas in karst regions. Furthermore, our investigations identified trace metals, in particular Hg, which were above drinking water guideline values, under certain precursor meteorological conditions.